Development and evaluation of a web system for the design of digital games with therapeutic potential by end users - Souza, Paula Maia de; Alves, Bianca Alessandra de Souza; Santos, Vinícius Matheus Romualdo; Proença, Fernando Roberto; Borges, Vânia de Oliveira; Neris, Vânia Paula de Almeida (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2024)
Additional therapy support for the treatment of Substance Use Disorders (SUDs) can be provided through digital games. However, we still face challenges in including people in SUDs rehabilitation in the digital game design process. This work seeks to minimize these challenges by investigating how to build a web system that guides end users in recovery from SUDs in digital game design activities with therapeutic potential. We used the Design Science Research method. To evaluate the system, we conducted a usability test with health professionals. The results suggest that healthcare professionals would use the system as an alternative therapy with their patients in SUDs rehabilitation because they saw therapeutic potential in the proposed solution.